APPLICATION OF INTRODUCTION TO PERSONALITY PSYCHOLOGY 5 GENETIC INTELLIGENCE THROUGH THE CONCEPT OF STIFIn TEST - Simanullang, Pernandus (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
Humankind continuously changes over time, whether as a result of environmental changes or human-driven inspiration. This includes everything from how people dress to how frequently they use the most recent technology. Many parents want to make their child the best child in history. Due to this, elders recommend that their children attend a school where they can receive a top-notch education that will be useful in the future. Older people value education more currently, but does this mean that enrolling them in the best schools will cost more money in the future? The best course of action is to see the potential of their child from the beginning and to motivate them to take care of them as adults. The most important thing for today's generation of children and youth is in school. However, the most important factor is the need for each person to be motivated and to use their full potential.